Globalization of Livelihood: Weakening of Caste-based Labor Regime of the Musahars - Giri, Madhu (Patan Prospective Journal, 2022)
Three central concerns motivated the authors to write this paper: first, to investigate how and why traditional livelihood strategies have been changing among the Musahars; second, to examine the local impacts of the globalization of labor and livelihood; and third, to look at the socio-cultural landscapes ofcaste-based occupations, and discrimination of the Musahar in central Tarai. The distribution of political-economic power in caste-based society is inherently unequal because caste base livelihood occupations generate unequal access to resources. More specifically, social, cultural, economic, and political relations in everyday life in multi-caste society have been changing. The rapid weakening and demise of pre-capitalist organizations of labor, commodity production, and reinvestment have led to a rapid diversification of modes of generation of livelihood at the household level. The large-scale migration from Tarai to India, from rural to urban areas and the international labor market maximizes livelihood opportunities of marginalized Musahars. They are broadly free to adopt multiple livelihood strategies but the constraints are again skill, economy, empowerment, and human capital. The second argument of the paper is globalization process, in the case of the Musahars, not only offers multiple options of livelihood ina trans-national free-market situation but also changes in the nature of the labour regime, such as widening wage disparity, increasing contractualization of work, skill-based segregation of work, the commodification of labor and body. In an era of globalization, the Musahars of Siraha internalized opportunities of migration, cultural campaigning to defend local identity, and changes in traditional occupation and social relations as positive impacts.